Islamic Boarding Schools As A Basis For Character Education In The Industrial Revolution Era 4.0 - Zaki Ulien Nuha; Ahmad Afandi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
Pesantren have been the initiators of institutions that provide religious education, especially Islam in the archipelago, especially when Islamic da'wah developed in the 13th century. The distinctive pattern of education with the presence of a mosque, a kiai, books, lodges, and students makes it the only original education in the archipelago. The advantage of pesantren compared to other educational institutions is its emphasis on the education of noble moral character compared to the cognitive side. This paper employed the library research method. The data were collected by analyzing/exploring some journals, books, both printed and electronic documents, and other source information that relates to the research. Pesantren have their strategies and methods when dealing with human moral education. Not only as an institution for producing virtuous people, but Islamic boarding schools also have an important role in the social dimension of society and even become a cadre institution for future leaders as a consequence of their regular forging and training for santri regarding superior individual personalities. However, currently, the capability of pesantren with its success in educating moral character is being tested in the era of high technology development known as the Industrial Revolution 4.0. A term that describes the characteristics and characteristics of the community or generation in it which is certainly different from previous generations.